Religious Institutions and Personal Injury Compensation Claims for Abuse: The Noteworthy Significance of Insurance - Joseph Lee (Australian Journal of Law & Religion)
Many churches, religious schools, and care institutions have apologised for historical child sexual abuse and committed themselves to reparation and safeguarding. However, recent changes to legislation have resulted in a deluge of tort law claims, civil litigation, and work for lawyers. Religious leaders and devotees today bear the financial burdens of compensating for historical wrongs sometimes many decades old in times of meagre or no insurance coverage. This article recalls some relevant discussion at the Royal Commission into Institutional Responses to Child Sexual Abuse about the anticipated consequences for insurance. Next, there is an examination of judicial ideas about insurance in decisions relating to civil liability. Then, it provides a look at some commercial comparisons and the response of governments to the lack of insurance. The article further considers a case example of what happened to a major faith-based insurer after the legislative changes. Finally, some alternative perspectives are investigated alongside a look into the future.